If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -29 = 65 Reorder the terms: -29 + 9x = 65 Solving -29 + 9x = 65 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '29' to each side of the equation. -29 + 29 + 9x = 65 + 29 Combine like terms: -29 + 29 = 0 0 + 9x = 65 + 29 9x = 65 + 29 Combine like terms: 65 + 29 = 94 9x = 94 Divide each side by '9'. x = 10.44444444 Simplifying x = 10.44444444
| 4(2x+1)=9x+25-4x | | x^2+y^2+6y-x=-5 | | sin(-1)=sin(1) | | sin(-1)=-sin(1) | | 16-1/20d | | 6-4n=78 | | y^2=5x+6 | | 5f+8.12=10.19 | | n+3n-2=28 | | 3/8m=m32 | | 72.9/2.7 | | 180=10x+6 | | (x/3-2x)2=8 | | -2x-4=11/2 | | 180=2x^2+128 | | -2(x-2)=11/2 | | x/3-2x2=8 | | f(6)=5x-4 | | 0.5xL+w=4.8 | | 3x-10+5x=-4+8x-6 | | 6x-11=-3+7 | | b-7/7b-14 | | y+7x=10fory | | (-4,6);y=1/4x-5 | | 6x-1=-3x+7 | | 1+1+1+f+u+c+k=500 | | 3x-13=x+15 | | 3r=102 | | -5(11+4x)=-21 | | 5/2x-7=11/2 | | 2/9=x/63 | | 8(9+3x)=96 |